Routine Testing–Oriented Method for Evaluating Inductive Current Transformers Accuracy Under Harmonic Distortion, Based on Maximum Current Error and Phase Displacement - Michal Kaczmarek (IEEE Access)
In the case of the modern inductive current transformers the most important factor that have influence on their wideband accuracy is the self-distortion of the secondary current caused by the nonlinearity of the magnetization characteristic of the magnetic core. In response to the industry requirement to simplify the measuring procedure in this paper the idea is proposed to evaluate their transformation accuracy from tests made for increased frequency sinusoidal current with consideration of the impact of self-generated low-order higher harmonics. Moreover, this proposed method ensures simple and fast determination of the maximum values of current error and phase displacement for transformation of distorted current harmonics by inductive current transformers essential for accuracy class assessment. This is important due to the fact, that both the phase angles and the RMS values of higher harmonics depend on the source of disturbances in the power network and have significant influence on their transformation accuracy. Therefore, different results for different current distortion is possible and these multiple conditions should be considered for their reliable test of transformation accuracy for distorted currents. However, for accuracy class evaluation they are correctly represented by distorted waveform containing main component and single higher harmonics the maximum values of current error and phase displacement are determined. The presented analyses aim to justify the application of this simplified method for testing the transformation accuracy of inductive current transformers for harmonics of distorted currents in routine test in contrast to the full procedure required to be used in type test.